EFFICACY OF DIATOMACEOUS EARTH AND TEMPERATURE TO CONTROL THE MAIZE WEEVIL IN STORED MAIZE - CERUTI, Fabiane Cristina; LAZZARI, Sonia Maria Noemberg; LAZZARI, Flavio Antonio; PINTO JUNIOR, Airton Rodrigues (Scientia Agraria, 2008)
Treatment with diatomaceous earth (DE) is an efficient insect control technique in integrated pest management programs of stored grain. Its main advantages are: low toxicity to mammals and long lasting efficacy. The objective of this research was to evaluate the efficacy of DE under different doses and temperatures to control Sitophilus zeamais in stored maize. In vials with 100 g of clean and dry corn kernels, 30 non-sexed 7-14 day-old adults of S. zeamais were submitted to the following treatments in three replicates: DE (Keepdry®) at 500, 750 and 1000 mg kg-1, at 15, 25 and 30 °C. The mortality was evaluated from the 1st to the 28th day. After this period, the adults were removed and the progeny was kept until the 56th day, when the insects were counted and the grain moisture content evaluated. The effect of temperature on S. zeamais mortality was significant for the three DE doses. The 750 and 1000 mg kg-1 doses caused the highest mortality at 25 °C and 30 °C, but with no significant difference between them. The progeny development was significantly higher in the control compared to the treatments with DE; there was no significant difference in the number of progeny among the three DE doses at any of the temperatures studied. The results support the use of DE as an effective grain protectant against S. zeamais in stored corn.